2020
DOI: 10.14740/gr1301
|View full text |Cite
|
Sign up to set email alerts
|

Severe Sprue-Like Enteropathy and Colitis due to Olmesartan: Lessons Learned From a Rare Entity

Abstract: Olmesartan is an angiotensin II receptor blocker (ARB) drug approved in 2002 for the treatment of hypertension. Since 2012, there have been reports of a rare adverse effect suspected to be related to its use. The author presents a case of a 63-year-old female with refractory gastrointestinal (GI) symptoms including diarrhea with associated weight loss and severe electrolyte abnormalities necessitating hospitalization. An extensive inpatient evaluation ensued and was initially unremarkable. Esophagogastroduoden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 17 publications
1
20
0
1
Order By: Relevance
“…We have thus performed a systematic literature search in Medline up to October 2020, using the following strings: “olmesartan enteropathy”, “olmesartan villous atrophy”, “olmesartan chronic diarrhoea”, “olmesartan malabsorption”, including only the 40 studies reporting gastric or colonic histopathologic evaluation on biopsies in addition to duodenal ones in humans were considered. Only English articles reporting data of OAE on humans were considered and summarised in Table 1 [1,8–46]. First, we found that villous atrophy was present in 93.5% of cases (61% villous atrophy, 32.4% PVA), confirming previously nonsystematic reported data [6].…”
Section: Discussionsupporting
confidence: 82%
“…We have thus performed a systematic literature search in Medline up to October 2020, using the following strings: “olmesartan enteropathy”, “olmesartan villous atrophy”, “olmesartan chronic diarrhoea”, “olmesartan malabsorption”, including only the 40 studies reporting gastric or colonic histopathologic evaluation on biopsies in addition to duodenal ones in humans were considered. Only English articles reporting data of OAE on humans were considered and summarised in Table 1 [1,8–46]. First, we found that villous atrophy was present in 93.5% of cases (61% villous atrophy, 32.4% PVA), confirming previously nonsystematic reported data [6].…”
Section: Discussionsupporting
confidence: 82%
“…However, no follow-up colon biopsy was performed in all three cases. Bashari DR et al also reported a case of olmesartan-associated spruelike enteropathy complicated with collagenous colitis, but they did not report a follow-up CS [15]. Ebrahim VS et al reported that collagenous colitis was observed in 2 of 3 cases, and in 1 case, a reexamination was performed 4 months after the withdrawal of olmesartan, and it is mentioned that histopathological improvement was observed [16].…”
Section: Discussionmentioning
confidence: 99%
“…olmesartan discontinuation [15]. Some patients with collagenous colitis showed a typical histology but had no symptoms [18].…”
Section: Abbreviationsmentioning
confidence: 99%
“…The final diagnosis was reached after a median of 5 months, and an acute onset of symptoms leading to diagnosis was present in 10% of patients. Coeliac serology results were reported in 140/183 5,11,13,14,[16][17][18][19][20][21][22]24,25,[27][28][29][30][31][32][33][34][35][36][37][38][39][40]83,84,86,[89][90][91][92][94][95][96][97][98][99][100][101] and were negative in the large majority of cases (138/140, 99%). In only two patients, IgA tissue transglutaminase antibodies were borderline and considered to be irrelevant by the authors.…”
Section: Baseline Clinical Featuresmentioning
confidence: 99%